ISOTONIC BEVERAGE EFFECT ON SURFACE HARDNESS OF BULK-FILL TYPE COMPOSITE RESIN - Norliana Afrianti; Isyana Erlita; Rosihan Adhani (FKG Unlam, 2019)
Background: Bulk-fill composite resin is a restorative material that can be applied directly to a cavity with 4 mm thickness. This benefits the dentist because it can accelerate restoration process. Isotonic drinks are one of soft drink categories that are popular among Indonesian people. This drink has an acidic pH and there are several other chemical contents that may affect the surface hardness of bulk-fill type composite resin. Purpose: The purpose of the study was to analyze changes in the hardness of bulk-fill composite resin surface after the immersion in isotonic drinks. Method: The type of this research was a true experimental study with post-test only and control group design. The shape of bulk-fill composite resin samples was cylinder with 10 mm diameter and 4 mm thickness. The study consisted of 3 treatment groups. The first group was immersed in isotonic drink A, the second group was immersed in isotonic drink Mizone and the third group was immersed in steriled distilled water for 18 hours respectively. The surface hardness was then measured using Vickers Microhardness Tester. Results: The result of One Way ANOVA and Bonferroni Post-Hoc test showed p value < 0.05, which means that there is a significant difference in the hardness of bulk-fill composite resin surface after the immersion in isotonic drink A and isotonic drink Mizone. Conclusion: Bulk-fill composite resin immersed in Mizone has the lowest hardness value than those immersed in drink A and distilled water.